Mothers’ and fathers’ lived experiences of postpartum depression and parental stress after childbirth: a qualitative study - Johansson, Maude (Int J Qual Stud Health Well-being, 2020)
Purpose: The study aims are to explore the lived experiences of mothers and fathers of postpartum depression and parental stress after childbirth. Methods: Qualitative interviews conducted, and analysed from an interpretative phenomenological analysis (IPA) perspective. Results: Both mothers and fathers described experiences of inadequacy, although fathers described external requirements, and mothers described internal requirements as the most stressful. Experiences of problems during pregnancy or a traumatic delivery contributed to postpartum depression and anxiety in mothers and affected fathers’ well-being. Thus, identifying postpartum depression with the Edinburgh Postnatal Depression Scale, mothers described varying experiences of child health care support. Postpartum depression seemed to affect the spouses’ relationships, and both mothers and fathers experienced loneliness and spouse relationship problems. Experiences of emotional problems and troubled upbringing in the parents’ family of origin may contribute to vulnerability from previous trauma and to long-term depressive symptoms for mothers. Conclusions: The findings of this study demonstrate the significant impact of postpartum depression and parental stress has in parents’ everyday lives and on the spouse relationship. These results support a change from an individual parental focus to couples’ transition to parenthood in child health care.